2022
DOI: 10.1002/tea.21747
|View full text |Cite
|
Sign up to set email alerts
|

A review of literature that uses the lens of the next generation science crosscutting concepts: 2012–2019

Abstract: New reforms in science education call for threedimensional learning by integrating disciplinary core ideas, science and engineering practices, and crosscutting concepts (CCCs). These reforms defined the new term, crosscutting concept (CCC), as a lens that has explanatory power across disciplines. To describe how researchers are examining and using the CCCs related to science teaching and learning, a literature review was conducted to identify articles that included the term "crosscutting concept" since its int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Similarly, Tsurusaki et al (2013) showed how the teacher's use of transformative boundary objects to leverage students' cultural knowledge and experience within science instruction, promoted context where traditional boundaries between students' lives and school science are blurred, and a critical consciousness about how the food system works and its connections to their everyday food choices is supported. Fick and Arias (2022) acknowledged the role that crosscutting concepts (NRC, 2012) can serve as tools for identifying and including students' FoK within science instruction. Brown (2017) found that scientific practices, particularly the development, and use of scientific models, can also bridge the school-home dichotomy by leveraging family and community FoK and creating a space where students can examine and explain scientific concepts using both Western science and Indigenous Knowledge perspective.…”
Section: Third Space and Fokmentioning
confidence: 99%
“…Similarly, Tsurusaki et al (2013) showed how the teacher's use of transformative boundary objects to leverage students' cultural knowledge and experience within science instruction, promoted context where traditional boundaries between students' lives and school science are blurred, and a critical consciousness about how the food system works and its connections to their everyday food choices is supported. Fick and Arias (2022) acknowledged the role that crosscutting concepts (NRC, 2012) can serve as tools for identifying and including students' FoK within science instruction. Brown (2017) found that scientific practices, particularly the development, and use of scientific models, can also bridge the school-home dichotomy by leveraging family and community FoK and creating a space where students can examine and explain scientific concepts using both Western science and Indigenous Knowledge perspective.…”
Section: Third Space and Fokmentioning
confidence: 99%
“…First, we introduce more sophisticated instructional practices over time as teachers develop a firmer grasp of the curriculum specifically and NGSS instruction with MLs broadly. For example, whereas three‐dimensional learning is emphasized from the outset of the PD program, CCCs tend to take a backseat to SEPs and DCIs in teachers' instructional practices (Fick & Arias, 2022). Thus, one focus of PD with returning teachers is making CCCs explicit in ways that harness the resources that all students, and MLs in particular, bring to the classroom (Nordine & Lee, 2021).…”
Section: Conceptual Framework For Pd Programsmentioning
confidence: 99%
“…The first strand informing our design approach relates to the challenge of integrating systems thinking in instructional materials (Fick, 2018; Fick & Arias, 2022) in order to address the diverse disciplinary fields that constitute climate science (Ledley et al, 2017). We define systems thinking as “a set of analytic skills used to improve the capability of identifying and understanding systems, [and] predicting their behaviors” (Arnold & Wade, 2015, p. 675).…”
Section: Literature Reviewmentioning
confidence: 99%